Św. Brygida – cykl obrazów w kościele Wniebowzięcia NMP Zwycięskiej w Lublinie - Kwiatkowska-Frejlich, Lidia (Archiwa, Biblioteki i Muzea Kościelne, 2015)
In the first half of the17th century, the stalls with the paintings in their backs showing episodes of the life of St. Bridget of Sweden were introduced into the chancel of the church of the Bridgettines in Lublin. The first series depicted seven paintings on the north wall and one on the east one at the high altar, the other series was made up of one picture on the east wall and six in southern wall. However, those who were present in the church watched only the fragment of the cycle, as they were allowed to be only in the area especially marked for them. A brief analysis of the iconographic representations shows that the scenes of the cycle, arranged in historical narrative, additionally provided the content that in the particular fragment was intended for specific groups. The nuns staying in the upper or lower choir saw the images around the high altar; the pictures both encouraged the Bridgettines to take the right path of spirituality and showed that the monastic rule was given to St. Bridget by Jesus in a supernatural way. Nuns’ fathers confessors – the Bernardines or Dominicans - benefited from the stalls in the chancel - they could watch the cycle as a whole and appreciate the effectiveness of Bridgittines’ path of spirituality. Novices had their place in the only chapel of the church. They looked at those fragments which depicted the hardships of religious life; the aim of the images was to discourage novices from joining the monastery, which was in accordance with the traditional attitude towards them in that religious order. The faithful who gathered in the only side aisle in that church could see the paintings which showed the life of the Bridgettines.